Efektivitas Pendidikan Kesehatan Snowball Throwing dan Buzz Group terhadap Pengetahuan tentang SADARI pada Remaja Putri - Nisa Ramadan Setianingrum; Ulfah Musdalifah; Hanifa Andisetyana Putri (Poltekkes Kemenkes Semarang, 2026)
Background: In 2022, the World Health Organization (WHO) reported 2.3 million new breast cancer cases among women. In Central Java, 10.530 cases were recorded in 2019, and in Semarang City, 1.725 cases were reported in community health centers and 3.111 in hospitals. Breast cancer may lead to organ dysfunction and death, highlighting the importance of early detection through Breast Self-Examination (BSE). Low awareness and practice of BSE are primarily due to a lack of knowledge. Health education using cooperative learning methods such as Snowball Throwing and Buzz Group is expected to improve knowledge of BSE. Methods: The research method used is a true experimental design with a two-group pretest-posttest design. The population consisted of 191 individuals, with 72 respondents selected using stratified random sampling and randomly assigned to two groups via spinner. Each group receives a different educational method. Results: The results showed a significant increase in knowledge in both groups after the intervention (p-value = 0.000). A Mann-Whitney test revealed a significant difference in effectiveness between the two methods (p-value = 0.04). The mean knowledge score difference was 9.75, indicating that the Snowball Throwing method was more effective than the Buzz Group method. Conclusion: There is a difference in the effectiveness of the level of knowledge about BSE in adolescent girls before and after being given health education Snowball Throwing and Buzz Group.